MORPHOMETRIC MEASUREMENT AS AN INDEX FOR ESTIMATING YIELD OF MEAT IN SHELL FISHES I. CRAB (SCYLLA SERATA) FORSKAL - GEORGE, CHINNAMMA; UNNITHAN, G RAJAGOPALAN (Fishery Technology, 2017)
Sixty one observations on length-breadth and whole weight-meat weight relations of India crab (Scylla serrata) were made. From the length of crab (cm) the whole weight (gm) can be computed by the equation:            log W = -0.1708 + 2.3341 log LSimilarly for any given length (cm) the meat weight (gm) can be found by the relation,            log w = -1.5745 + 3.0148 log L